The effectiveness of given financial resources for the additional Thermal insulation of buildings - Potocek, Karol (Communications - Scientific letters of the University of Zilina, 1999)
Current development of material base and technology enables different ways to improve heat-insulating properties of existing packing constructions of the building. Particular ways are different among themselves concerning the service life. This contribution deals with the appreciation of additional thermal insulation while taking into account the return of financial expenses in the relation to its service life. Basic calculation formulas and their graphical illustration (which gauges economical effectiveness) are presented.